Chronic lymphocytic leukemia nurse-like cells express hepatocyte growth factor receptor (c-MET) and indoleamine 2,3-dioxygenase and display features of immunosuppressive type 2 skewed macrophages - Paolo Giannoni; Gabriella Pietra; Giorgia Travaini; Rodolfo Quarto; Genti Shyti; Roberto Benelli; Laura Ottaggio; Maria Cristina Mingari; Simona Zupo; Giovanna Cutrona; Ivana Pierri; Enrico Balleari; et al. (Haematologica, 2014)
Hepatocyte growth factor, produced by stromal and follicular dendritic cells, and present at high concentrations in the sera of patients with chronic lymphocytic leukemia, prolongs the survival of leukemic B cells by interacting with their receptor, c-MET. It is, however, unknown whether hepatocyte growth factor influences microenvironmental cells, such as nurse-like cells, which deliver survival signals to the leukemic clone. We evaluated the expression of c-MET on nurse-like cells and monocytes from patients with chronic lymphocytic leukemia and searched for phenotypic/functional features supposed to be influenced by the hepatocyte growth factor/c-MET interaction. c-MET is expressed at high levels on nurse-like cells and at significantly higher levels than normal on monocytes from patients. Moreover, the hepatocyte growth factor/c-MET interaction activates STAT3TYR705 phosphorylation in nurse-like cells. Indoleamine 2,3-dioxygenase, an enzyme modulating T-cell proliferation and induced on normal monocytes after hepatocyte growth factor treatment, was detected together with interleukin-10 on nurse-like cells, and on freshly-prepared patients’ monocytes. Immunohistochemical/immunostaining analyses demonstrated the presence of c-MET+ and indoleamine 2,3-dioxygenase+ cells in lymph node biopsies, co-expressed with CD68 and vimentin. Furthermore nurse-like cells and chronic lymphocytic monocytes significantly inhibited T-cell proliferation, prevented by anti-transforming growth factor beta and interleukin-10 antibodies and indoleamine 2,3-dioxygenase inhibitors, and supported CD4+CD25high+/FOXP3+ T regulatory cell expansion. We suggest that nurse-like cells display features of immunosuppressive type 2 macrophages: higher hepatocyte growth factor levels, produced by leukemic or other microenvironmental surrounding cells, may cooperate to induce M2 polarization. Hepatocyte growth factor may thus have a dual pathophysiological role: directly through enhancement of survival of the leukemic clone and indirectly by favoring T-cell immunosuppression.